Cultures. Conflict - Analysis - Dialogue. Proceedings of the 29th International Ludwig Wittgenstein-Symposium in Kirchberg, Austria - Runggaldier, Edmund (Publications of the Austrian Ludwig Wittgenstein Society - New Series (N.S.), 2013)
What can systematic philosophy contribute to come from conflict between cultures to a substantial dialogue? - This question was the general theme of the 29th international symposium of the Austrian Ludwig Wittgenstein Society in Kirchberg. Worldwide leading philosophers accepted the invitation to come to the conference, whose results are published in this volume, edited by Christian Kanzian Edmund Runggaldier. The sections are dedicated to the philosophy of Wittgenstein, Logics and Philosophy of Language, Decision- and Action Theory, Ethical Aspects of the Intercultural Dialogue, Intercultural Dialogue, and last not least to Social Ontology.